Evidence of nickel ions dimerization in NiWO4 and NiWO4 – ZnWO4 solid solutions probed by EXAFS spectroscopy and reverse Monte Carlo simulation - Bakradze, Georgijs; Kalinko, Aleksandr; Kuzmin, Alexei (Elsevier, 2021)
The existence of exchange-coupled Ni ions – the so-called magnetic dimers – in wolframite-type NiWO and ZnNiWO solid solutions with high nickel content was discovered by X-ray absorption spectroscopy combined with reverse Monte Carlo (RMC) simulations. Temperature- (10–300 K) and composition-dependent X-ray absorption spectra were measured at the Ni K-edge, Zn K-edge, and W L-edge of microcrystalline NiWO, ZnNiWO and ZnWO. Structural models were obtained from simultaneous analysis of the extended X-ray absorption fine structure (EXAFS) spectra at three metal absorption edges using RMC simulations. The obtained radial distribution functions for different atomic pairs made it possible to trace in detail the changes in the local environment of metal ions and the effect of thermal disorder. Dimerization of Ni ions within quasi-one-dimensional zigzag chains of [NiO] octahedra was evidenced in NiWO in the whole studied temperature range. It manifests itself as the splitting of the Ni–Ni radial distribution function into two separate peaks. The effect is further preserved in solid solutions ZnNiWO for , which is related to the probability to find two Ni ions in neighbouring positions.---- / / / ---- This is the preprint version of the following article: Georgijs Bakradze, Aleksandr Kalinko, Alexei Kuzmin,Evidence of nickel ions dimerization in NiWO and NiWO-ZnWO solid solutions probed by EXAFS spectroscopy and reverse Monte Carlo simulations, Acta Materialia, Volume 217, 117171 (2021), DOI https://doi.org/10.1016/j.actamat.2021.117171, which has been published in final form at https://www.sciencedirect.com/science/article/abs/pii/S1359645421005516, under the CC BY-NC-ND license.
G.B. acknowledges the ﬁnancial support provided by the State Education Development Agency for project No.1.1.1.2/VIAA/3/19/444 (agreement No. 1.1.1.2/16/I/001) realized at the Institute of Solid State Physics, University of Latvia. A.K. and A.K. would like to thank the support of the Latvian Council of Science project No. lzp-2019/1-0071. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; NiWO4; ZnWO4; antiferromagnets; EXAFS; reverse Monte Carlo; solid solutions